2009
DOI: 10.1111/j.1471-6712.2007.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perceptions as an indicator of quality of care, in Greek patients with inflammatory bowel disease

Abstract: The assessment of the quality of health care, based on patients' perception, revealed quality problems in the dimensions of accommodation, accessibility and information. According to subgroup analysis, disease type, educational status, age and disease duration play an important role in the formation of patients' expectations from the healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
(38 reference statements)
1
9
0
1
Order By: Relevance
“…, Pallis et al . , Masachs et al . ) revealed that persons with IBD reported suboptimal care in areas such as accommodation, accessibility and information, as well as psychological and physical well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…, Pallis et al . , Masachs et al . ) revealed that persons with IBD reported suboptimal care in areas such as accommodation, accessibility and information, as well as psychological and physical well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the patient is important also in the evaluation of the quality of health care and nursing. From this perspective, there are evaluations using satisfaction instruments, analysing patients' experiences during the caring process, combining patients' experiences with their expectations and asking patients to describe good nursing care . Furthermore, analyses about factors connected with the quality of nursing care have produced inconsistent results; these have to do, for example, with staffing levels, skill mix and nurse autonomy, and nurses' time pressure .…”
Section: Introductionmentioning
confidence: 99%
“…The existing knowledge about IBD and quality of care is based on studies measuring quality of care with predefined questions (86,88). Results from the QUOTE-IBD studies showed that the lowest importance scores were observed for autonomy, costs and accessibility.…”
Section: Assessing Quality Of Carementioning
confidence: 99%
“…Results from the QUOTE-IBD studies showed that the lowest importance scores were observed for autonomy, costs and accessibility. The three most important aspects of quality of care for IBD patients were competence, accommodation and courtesy (86,88). In the Portuguese version of the QUOTE-IBD, it was concluded that there is no golden standard for the assessment of quality of care from the perspective of those living with IBD.…”
Section: Assessing Quality Of Carementioning
confidence: 99%
See 1 more Smart Citation